Safety and efficacy of unilateral and bilateral pedicle screw fixation for lumbar degenerative diseases by transforaminal lumbar interbody fusion: An updated systematic review and meta-analysis - Zhong, Rui; Xue, Xiali; Wang, Runsheng; Dan, Jing; Wang, Chuanen; Liu, Daode (Frontiers in Neurology, 2022)
Background: The purpose of this study was to compare the safety and efficacy of unilateral versus bilateral pedicle screw fixation (BPSF) for lumbar degenerative diseases. Methods: Electronic databases including PubMed, Web of science, the Cochrane Library, Scopus, MEDLINE, EMBASE, EBSCO were searched by computer. The deadline was set for June 1, 2022. This study included all high-quality randomized controlled trials (RCTs), prospective clinical controlled studies (PRO), and retrospective studies (Retro) that compared unilateral and bilateral pedicle screw fixation in the treatment of lumbar degenerative diseases. Revman5.3 software was used for meta-analysis after two researchers independently screened the literature, extracted data, and assessed the risk of bias in the study. Results: 14 studies with a total of 1086 patients were included. Compared with BPSF, unilateral pedicle screw fixation (UPSF) has shorter operation time and hospital time, and less blood loss and operation cost, operation time [SMD=-1.75, 95%CI (-2.46 to -1.03), P<0.000 01], hospital time [SMD=-1.10, 95%CI (-1.97 to -0.22), P=0.01], Blood loss [SMD=-1.62, 95%CI (-2.42 to -0.82), P<0.000 1], operation cost [SMD=-14.03, 95%CI (-20.08 to -7.98), P<0.000 01], the ODI after bilateral pedicle screw fixation was lower, and the degree of lumbar dysfunction was lighter, [SMD=0.19, 95%CI (0.05 to 0.33), P=0.007], better fusion effect, fusion rate [RR=0.95, 95%CI (0.91 to 1.00), P=0.04]. VAS-Low back pain [SMD=0.07, 95%CI (-0.07 to 0.20), P=0.35], VAS-Leg pain [SMD=0.18, 95%CI (-0.00 to 0.36), P=0.05], SF-36 [SMD=0.00, 95%CI (-0.30 to 0.30), P=1.00], complications rate [RR=0.94, 95%CI (0.9154 to 1.63), P=0.82], the overall difference was not statistically significant. Conclusions: Currently limited evidence suggests that UPSF significantly reduces blood loss, significantly shortens the operative time and hospital stay, and reduces blood loss and costs. After BPSF, the ODI was lower, the degree of lumbar spine dysfunction was lower, and the fusion rate was significantly higher. The VAS, SF-36, and complications scores of the two groups were comparable, and there was no significant clinical difference.